Development and validation of the Information Literacy Measurement Scale (ILMS-34) in Chinese public health practitioners - Hui Li; Ke-Ying Li; Xia-Rong Hu; Xuan Hong; Yan-Ting He; Hua-Wei Xiong; Yi-Li Zhang (BMC Medical Education)
Abstract Background Public health professionals (PHPs) have increasing information needs to inform evidence-based public health decisions and practice, which requires good information literacy. A comprehensive and reliable assessment tool is necessary to assess PHPs' literacy and guide future promotion programs. However, there is a lack of measurement tools specifically for the information literacy of PHPs. Objectives This study aimed to develop an information literacy assessment tool for PHPs and test its psychometric properties among PHPs. Methods A 34-item Information Literacy Measurement Scale (ILMS-34) for PHPs was developed based on an extensive literature review, the Delphi method, and pilot testing. The ILMS-34 was further validated among 526 PHPs recruited from four cities in Guangdong Province, China, using convenience sampling. The sample was randomly divided into two equal groups for exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), respectively. Other psychometric testing included item analysis, Cronbach's α coefficient, three-week test–retest reliability, and known-group validity. Results EFA yielded four dimensions for the ILMS-34: information consciousness, information knowledge, information ability, and information ethics. Subsequent CFA showed a good model fit of the four-factor structure (χ2/df = 1.485, RMSEA = 0.043, SRMR = 0.038, TLI = 0.977, CFI = 0.979). There were significant differences in each item between the high and low-scoring groups (p < 0.001), indicating good item discrimination. The ILMS-34 demonstrated good internal consistency with a Cronbach's α coefficient of 0.97 for the total scale (four subscales: 0.92, 0.92, 0.98, and 0.91, respectively). It also showed good test–retest reliability after three weeks with an ICC coefficient of 0.67. The DSE-MS scores varied by various sample characteristics, verifying the known-group validity. Conclusion The ILMS-34 is a multidimensional instrument with good psychometric properties and can be used as an effective tool to measure information literacy among PHPs. Further validation in other samples across various cultures is needed to test its broad application.